DESENVOLVIMENTO DE UMA METODOLOGIA ELETROANALÍTICA PARA A DETERMINAÇÃO DE GLIFOSATO EM AMOSTRAS AMBIENTAIS. - Santos, Simone Carla dos (2012)
This paper describes the development of an electroanalytical methodology for the determination of the pesticide glyphosate in environmental samples. The results obtained by square wave voltametry (SWV) in NaNO2 0,10 mol Lˉ¹ (pH 6,5) about hanging mercury drop electrode (HMDE) showed that glyphosate has not electroactive response. Thus, the electroactivity of glyphosate was obtained by complexation with Cu²+ ions. The complex formed Cu (II) - glyphosate showed only a reduction peak at - 0,1 V with almost reversible process controlled by diffusion of the species on the electrode surface. The voltammetric and experimental parameters involved in the electrochemical reduction were optimized and the best responses were: NaNO2 supporting electrolyte of 0,10 mol Lˉ¹ at pH 6,5, concentration of Cu (II) of 2,61 x 10-7 mol Lˉ¹, pre-concentration time 120 sec. The parameters were SWV frequency = 100 sec-1, amplitude = 50 mV and increase of sweep = 6mV. After the system optimization, calibration curves were constructed and the detection limit (LD) and quantification limit (LQ) obtained were 22,04 μg Lˉ¹ ± 0,42 and 73,46 μg Lˉ¹ ± 1,41, respectively. The recovery tests showed values of 100,27% ± 1,96 in electrolyte and 99,12% ± 2,14 in water. Additionally, the methodology was applied for determination of glyfhosate in water sample collected in the creek from the Santa Clara, in the municipality of Candói/PR, with a value of 311,09 μg Lˉ¹ glyphosate. Interference study was performed from the humic acid and it was found that there was a complex between the Cu (II) and humic acid, shifting the potential for negative regions. The presence of humic acid with the complex Cu (II) - glyphosate causes an increase in the current intensity also led to an increase in the width of the potential. Although the interference xi seen, the percentage recovery in the sample examined were above 99% so the glyphosate can be measured in samples of water by the proposed method.